THE INFLUENCE OF SERVICE QUALITY AND PRODUCT QUALITY ON CUSTOMER SATISFACTION (CASE STUDY OF MAMI LAMPUNG EATING HOUSE) - Mustofa, Ahmad; Azizah, Ana Chosiatul; F Sanjaya, Vicky (Journal for Management Student (JFMS), 2023)
This research aims to determine the influence of service quality, namely: Physical evidence (tangibles); Reliability (reliability); Responsiveness (responsiveness); Guarantee (assurance); Empathy, as well as the influence of product quality, namely: 1) Performance is related to the basic operating characteristics of a product. 2) Durability on customer satisfaction at the Mami Lampung restaurant with a sample of 93 customers. The sample was carried out by collecting data through a questionnaire. Data analysis uses PLS analysis which shows the results that service quality and product quality have a positive and significant effect on customer satisfaction. Keywords : Service Quality; Product Quality; Customer Satisfaction; Restaurant